2022
DOI: 10.21203/rs.3.rs-1458267/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of ICT hardware, software and FDI on CO2 emissions in China

Abstract: With the rapid development of information and communication technology (ICT) and counter-cyclical expanding of foreign direct investment (FDI), most foreign-invested companies in China are highly polluting. Meanwhile, new research shows that the impact of ICT on the environment is uncertain. This study is an effort in dividing ICT into hardware and software, aiming to explore its effects on CO2 emissions from 2003 to 2017 in 31 provinces, autonomous regions and municipalities in China, and further explore the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The findings showed that institutional quality and ICT had negative impact on carbon emission. For China, (Chi & Meng, 2022) explored the effect of ICT on CO2 emission in different provinces and municipalities and concluded that ICT reduced CO2 emission in System GMM estimation. (Kongbuamai et al, 2022) studied the nexus between ICT and ecological footprints in N-11 countries by applying Feasible Generalized Least Squares and Driscoll-Kraay standard errors and found that ICT had positive association with ecological footprints in N-11 countries.…”
Section: Ict and Environmental Performancementioning
confidence: 99%
“…The findings showed that institutional quality and ICT had negative impact on carbon emission. For China, (Chi & Meng, 2022) explored the effect of ICT on CO2 emission in different provinces and municipalities and concluded that ICT reduced CO2 emission in System GMM estimation. (Kongbuamai et al, 2022) studied the nexus between ICT and ecological footprints in N-11 countries by applying Feasible Generalized Least Squares and Driscoll-Kraay standard errors and found that ICT had positive association with ecological footprints in N-11 countries.…”
Section: Ict and Environmental Performancementioning
confidence: 99%